2013
DOI: 10.4095/292837
|View full text |Cite
|
Sign up to set email alerts
|

Till geochemical signatures of the Sisson W-Mo deposit, New Brunswick

Abstract: A till composition study was carried out around the Sisson W-Mo deposit, one of the largest W deposits in the world, as part of the Geological Survey of Canadamp;gt;'s (GSC) Targeted Geoscience Initiative 4 (TGI-4), a collaborative federal geoscience program with a mandate to provide industry with the next generation of geoscience knowledge and innovative techniques that will result in more effective targeting of buried mineral deposits. This till geochemical study is one of the first detailed studies around a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Geochemical data for all samples analyzed in this study are reported in McClenaghan et al (2013b). Appendix A lists a subset of these data that includes only surface till samples within or proximal to the southeast-trending glacial dispersal train defined by Seaman (2003).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Geochemical data for all samples analyzed in this study are reported in McClenaghan et al (2013b). Appendix A lists a subset of these data that includes only surface till samples within or proximal to the southeast-trending glacial dispersal train defined by Seaman (2003).…”
Section: Resultsmentioning
confidence: 99%
“…The highest values occur in till over the deposit (239 to 261 ppm) and 2 km southwest of the deposit (247 ppm, sample CS-T09). Slightly elevated Zn values (98 to 177 ppm) occur in till over Tetagouche Group sedimentary rocks southeast and northeast of the deposit (McClenaghan et al 2013b). Zinc displays strong (r>0.8) positive correlation with Cd, In, and Pb, and moderate (r=0.6-0.8) correlations with W, Sn, Cu, Ag, Bi, and Te (Table 2).…”
Section: Arsenic Zinc and Cadmium In The <0063 MM Fraction Of Tillmentioning
confidence: 99%
See 3 more Smart Citations